Low-Density Lipoproteins-Cholesterol Prevalence and Risk Factors: An Examination of the 2015–2016 National Health and Nutrition Examination Survey in the United States - Tambe E. Akem; Marianne Cuéllar (Public Health, 2025)
Background Non-communicable diseases (NCDs) are the leading cause of mortality worldwide, with cardiovascular diseases (CVDs) being the most predominant. This is a similar trend in the United States (U.S.). Modifiable and non-modifiable factors are important determinants of dyslipidaemia, a known cause of CVDs. Objective This study aimed to explore the pattern of high-density lipoprotein cholesterol (HDL-C) distribution and its associated risk factors. Methods The data was collected from the National Health and Nutrition Examination Survey (NHANES) 2015-2016 database which is part of the yearly cross-sectional survey. The NHANES uses complex multistage probability sampling method in data collection. The target population was the noninstitutionalized civilian living across the U.S. The primary sampling units were individuals. Socio-demographic characteristics, body measurement (waist circumference) and blood samples (to determine HDL-C and total cholesterol levels) were recorded. In the database, 5000 respondents were randomly selected for analysis. Statistical analyses were performed using Stata version 14.0. The results are described as means and standard deviation (SD) for group and continuous variables. Regression analyses were used to identify risk factors of low HDL-C. Results Of the complete cases (3989), 49.03% were males. The mean age was 46.57±15.44-years. The mean HDL-C was 1.39±0.45 mmoL/L. The prevalence of low HDL-C was 32.8% in males and 12.5% in females. The results obtained from multiple linear regression indicated that male gender, age, ethnicity, country of birth, number of children aged 0-18-years per household, waist circumference, family income to poverty ratio and total cholesterol were significantly associated with HDL-C. Multivariable logistic regression revealed male gender, age 30 to 49-years, ethnicity, smoking, enlarged waist circumference (cm), low family income to poverty ratio and high total cholesterol were associated with low HDL-C. Conclusion The prevalence of low HDL-C of was 22.4 %. This was distributed into 32.8% in males and 12.5% in females. The associated risk factors show that lifestyle modification is important in the prevention of low HDL-C and consequently, CVDs.